2022
DOI: 10.13189/ujar.2022.100602
|View full text |Cite
|
Sign up to set email alerts
|

CROP Rotation and Diversity Practices among Rural Farmers in Ebonyi State, Nigeria

Abstract: Crop rotation has been identified as a practice that enhances soil fertility and healthy foods, but its awareness and adoption among rural farmers of Ebonyi State, who need the knowledge of best agronomic practices owing to the high cost of fertilizer, remain unknown. To bridge this gap, 180 rural farmers were selected for this study using a multi-stage sampling procedure. Data for the study was obtained using a structured interview schedule, and was analyzed with the use of descriptive statistics, chi-square,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…This suggests that farmers are exposed to information on CSA practices, input delivery, and credit access, resulting in increased adoption. These findings conform to (Anik et al, 2021;Aryal et al, 2018;Danso-Abbeam, 2022;Igberi et al, 2022;Obeng, E., A. Weber, 2014), who reported the positive influence of extension services on minimum tillage, crop rotation, intercropping, agroforestry, and drought-tolerant varieties across different countries. On the other hand, Tufa et al (2023) found that extension services did not have a significant relationship with minimum tillage, and they attributed it to poor delivery services from extension agents and farmers' lack of confidence in their skills.…”
Section: The Influence Of the Use Of Seasonal Climate Forecast And We...supporting
confidence: 86%
“…This suggests that farmers are exposed to information on CSA practices, input delivery, and credit access, resulting in increased adoption. These findings conform to (Anik et al, 2021;Aryal et al, 2018;Danso-Abbeam, 2022;Igberi et al, 2022;Obeng, E., A. Weber, 2014), who reported the positive influence of extension services on minimum tillage, crop rotation, intercropping, agroforestry, and drought-tolerant varieties across different countries. On the other hand, Tufa et al (2023) found that extension services did not have a significant relationship with minimum tillage, and they attributed it to poor delivery services from extension agents and farmers' lack of confidence in their skills.…”
Section: The Influence Of the Use Of Seasonal Climate Forecast And We...supporting
confidence: 86%